Dissolved major ions, Sr and 87Sr/86Sr of coastal lakes from Larsemann hills, East Antarctica: Solute sources and chemical weathering in a polar environment. Issue 11 (5th March 2020) - Nuruzzama, Mohammad; Rahaman, Waliur; Tripathy, Gyana R.; Mohan, Rahul; Patil, Shramik
Abstract: Dissolved major ions, Sr concentrations and 87 Sr/ 86 Sr ratios of 10 coastal lakes from the Larsemann Hills, East Antarctica have been studied to constrain their solute sources, transport and glacial weathering patterns in their catchments. In absence of perennial river/streams, lakes serve as only reliable archive to study land surface processes in these low‐temperature regions. The lake water chemistry is mostly Na‐Cl type and it does not show any significant depth variations. Sr isotope compositions of these lakes vary from 0.7110 to 0.7211 with an average value of 0.7145, which is higher than modern seawater value. In addition to oceanic sources, major ions and Sr isotopic data show appreciable amount of solute supply from chemical weathering of silicate rocks in lake catchments and dissolution of Ca‐Mg rich salts produced during the freezing of seawaters. The role of sulphide oxidation and carbonate weathering are found to be minimal on lake hydro‐chemistry in this part of Antarctica. Inverse model calculations using this chemical dataset provide first‐order estimates of dissolved cations and Sr; they are mostly derived from oceanic (seawater + snow) sources (cations approximately 76%) and (Sr approximately 92%) with minimal supplies from weathering of silicates (cations approximately 15%); (Sr approximately 2%) and Ca‐rich minerals (cations approximately 9%); (Sr approximately 7%). The silicate weathering rate and its corresponding atmospheric CO2 consumption rate estimates for Scandrett lake catchment (3.6 ± 0.3 tons/km 2 /year and 0.5 × 10 5 moles/km 2 /year), are lower than that of reported values for the average global river basins (5.4 tons/km 2 /year and 0.9 × 10 5 tons/km 2 /year) respectively. The present study provides a comprehensive report of chemical weathering intensity and its role in atmospheric CO2 consumption in low‐temperature pristine environment of Antarctica. These estimates underscore the importance of Antarctica weathering on atmospheric CO2 budget, particularly during the past warmer periods when the large area was exposed and available for intense chemical weathering. Abstract : Antarctic lakes in Larsemann Hills, chemical affinity, their sources and silicate weathering rate in Antarctica.